Impact of a culinary medicine intervention on diet and health metrics in patients with type 2 diabetes and elevated body mass index - Natalia I. Heredia; Logan R. Thornton; Diana C. Guevara; Natalia Williams; Grace Marcelo-Ramirez; Joanne Chow; Lorna H. McNeill; Karen Basen-Engquist; Ruth Rechis; Deanna M. Hoelscher (PLoS ONE, 2026)
Purpose Culinary Medicine (CM), an educational approach blending the art of cooking with the science of medicine, has shown promise in improving diet and health outcomes. We conducted a mixed-methods, quasi-experimental evaluation of a CM program to promote cooking and healthy dietary intake. Methods Patients with type 2 diabetes and elevated body mass index (>25) were recruited from primary care clinics in low-income neighborhoods. The program, delivered by a dietitian, includes five weekly 90-minute sessions on basic cooking skills with behaviorally-based nutrition education. An explanatory sequential mixed-methods pilot study with a pre-post survey design and post-program interviews was used to assess improvements in dietary behaviors, nutrition knowledge, and cooking skills. Results A total of 89 individuals enrolled (58 intervention, 31 control). Fifty (86%) intervention participants attended the sessions, and 45 (78%) completed post-intervention surveys, while 22 (71%) control participants completed post-intervention surveys. Compared to control, the intervention group showed statistically significant improvements in perceived health (Adjusted Odds Ratio = 16.15, 95% CI 3.47,75.23, p < 0.001) and cooking self-efficacy (Adjusted β = 0.43, 95% CI 0.03,0.84, p = 0.04), and a decrease in perceived barriers to healthy eating (Adjusted β = − 0.64, 95% CI −1.21,-0.08, p = 0.03). We found a statistically significant decrease in HbA1c in the intervention group from pre- to post-test, though between-group comparisons were not statistically significant. All other behavioral, psychosocial, and biometric variables were non-significant but trended in the expected direction. Conclusions This study is feasible and acceptable. The CM program effectively promotes cooking skills and healthy eating among low-income patients with type 2 diabetes and elevated body mass index.